The Language instinct : the new science of language and main - Pinker, Steven (Penguin Books, 1995)
\'Dazzling...Pinker\'s big idea is that language is an instinct...as innate to us as flying is to geese...Words can hardly do justice to the superlative range and liveliness of Pinker\'s investigations\' - \"Independent\". \'A marvelously readable book...illuminates every facet of human language: its biological origin, its uniqueness to humanity, its acquisition by children, its grammatical structure, the production and perception of speech, the pathology of language disorders and the unstoppable evolution of languages and dialects\' - \"Nature\".
Keywords: humanitní vědy a umění